Новый вид рода Eurytoma Illiger (Hymenoptera, Chalcidoidea, Eurytomidae) из степной зоны СССР - Зерова, М.Д. (Вестник зоологии, 1980)
A new species Eurytoma stepposa sp. n. is described from the Steppe Zone of the USSR. A new species is bred from the stems of Stipa spp. infested by larvae of Tetra-mesa. Eurytoma stepposa sp. n. is closely allied to E. clavatula Zer., but differs in shape of face and abdomen. Holotype is in the collection of Institute of Zoology, Academy of Sciences, Ukrainian SSR, Kiev.